Doctraining mobile: um jogo sério para treinamento de estudantes de medicina em casos clínicos - Oliveira, Everton Jales de (Universidade Federal Rural do Semi-Árido, 2020)
The rapid expansion of the network of medical schools brought a deficit in the quality of teaching, due to the lack of infrastructure and resources in some universities, thus hampering the theoretical and practical training of students. However, with the significant advances in mobile technologies in recent years, educational institutions are providing new contexts and opportunities for learning and teaching. As an example, we can mention the growing use of serious games as an educational tool. Digital games, in addition to their playful and motivational aspects, have the potential for the development of many skills; however, they are still little used in formal education. Based on this context, a data survey was carried out with medical professors from UFERSA, to investigate new technological needs aimed at teaching and learning medical students, and, with that, it was possible to extract requirements that resulted in the development of a serious game called DocTraining Mobile. The game was developed for smartphones, with the objective of maximizing medical students' self-learning in clinical cases and general subjects in the area. The project was divided into two phases. The first involves the design and development activities of the game and, in the second, the activities of data collection and analysis for the process of learning evaluation and validation of the game, using the TAM (Technology Acceptance Model) method. The results showed positive indices in terms of game satisfaction, with most students positively evaluating both the ease of use and the perceived usefulness, in terms of learning. It was not possible to obtain conclusive results in terms of gains in student learning, but the tests showed evidence of gains in knowledge. As a contribution in the field of computing, there is the conception and development of DocTraining Mobile. In the educational field, there is the validation of the use of a serious game with medical students, with a focus on learning clinical cases, in addition to other subjects in the area.
Keywords: Jogos Sério; Autoaprendizagem; Aprendizagem Móvel; Medicina; Casos Clínicos; Serious Games; Self-Learning; Mobile Learning; Medicine; Clinical Cases; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO